Prevalence of Myasthenia progression in hepatic encephalopathy syndrome - Burhan Raoof1, Israa; E. Abdalah, Mayssaa (Al-Nahrain Journal of Science, 2020)
Hepatic encephalopathy (HE) is a neurological and psychological syndrome related to acute and chronic liver failure especially during cirrhosis, it is associated with over production of ammonia in gastrointestinal tract with failure excretion by the liver in addition to increased free radical and bacterial transmission have played an important role. A symptom of disease includes coma, ophthalmia, irregular sleeping, stress and difficult breathing. It may be develop to intestinal bleeding; reduced blood pressure and electrolyte disturbances. Myasthenia is early symptoms of muscle dystrophies and prevalence of antibodies against acetylcholine receptors, nicotine receptors, tyrosine kinase and low-density lipoprotein proteins thus severely weakening muscles and skeletons have been demonstrated, it is playing important role in myasthenia progressing especially after five years of liver antibodies detection. Recently, the treatment is mainly depending on the reduced intestinal ammonia with non-absorbent disaccha¬rides from intestine and MRI should be used to follow up in addition to newer immunosuppressive drugs such as Rifaxamin, an inhibitor of interleukins and steroids is very important to treat this disease.